2014
DOI: 10.1002/jps.24022
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-Stable Peptide-Coated Liposome Nanoparticles: A Proof-of-Concept Study with Opioid Fentanyl in Enhancing Analgesic Effects and Reducing Plasma Drug Exposure

Abstract: Previous we reported a novel pressurized olfactory drug (POD) delivery device that deposit aerosolized drug preferentially to upper nasal cavity. This POD device provided sustained CNS levels of soluble morphine analgesic effects. However, analgesic onset of less soluble fentanyl was more rapid but brief, likely due to hydrophobic fentanyl redistribution readily back to blood. To determine whether fentanyl incorporated into an aerosol stable liposome that binds to nasal epithelial cells will enhance CNS drug e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Cell association of NPs was also highly influenced by the surface density of cRGD. Similarly, other research groups have found that increasing RGD-densities on the surface of nanocarriers generally result in increasing binding to the integrin α v β 3 , coated on plate surfaces or present on the surface of cells [ 64 , 65 ]. In the present work, the NPs association to HUVECs increased with increasing RGD-densities and reached a maximum at ~118,000 RGD/µm 2 (density on the high cRGD-NPs).…”
Section: Discussionmentioning
confidence: 85%
“…Cell association of NPs was also highly influenced by the surface density of cRGD. Similarly, other research groups have found that increasing RGD-densities on the surface of nanocarriers generally result in increasing binding to the integrin α v β 3 , coated on plate surfaces or present on the surface of cells [ 64 , 65 ]. In the present work, the NPs association to HUVECs increased with increasing RGD-densities and reached a maximum at ~118,000 RGD/µm 2 (density on the high cRGD-NPs).…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, when the liposomes were administered to rats using the POD device, fentanyl plasma concentrations as well as those measured in the brain 5 min post-administration were lower than those obtained using free fentanyl (although not significantly different). However, when the analgesic effect was measured, the fentanyl-loaded RGD liposomes provided a slightly slower onset of action and a lower, but more prolonged, analgesic effect [ 175 ]. The decision to use in small animals a device optimized for deposition in the human nasal cavity is questionable.…”
Section: Targeting the Nasal Epithelium For Optimizing Nose-to-bramentioning
confidence: 99%
“…Nanoparticles have attracted interest in recent years because these systems act as carriers providing controlled and sustained drug delivery and increasing the drug's bioavailability and mean residence time (Sukhorukov et al, 2005). The pharmacodynamics and pharmacokinetics of nanoparticulated opioids administered by several routes, including orally, have been investigated in numerous species (Mystakidou et al, 2007;Paul-Murphy et al, 2009;Wang et al, 2009;Krugner-Higby et al, 2011;Hoekman et al, 2014;Han et al, 2015;Vazzana et al, 2015). However, to our knowledge, there are no studies reporting the possible antinociceptive effect of methadone administered orally to horses, as free drug or as nanoencapsulated formulation.…”
Section: Introductionmentioning
confidence: 99%